Homemade masks in the COVID-19 pandemic: recommendations, physical characteristics, disinfection and efficacy of use - Sousa, Iago Torres Cortês de (2021)
Objective: To describe the recommendations, physical characteristics, methods of disinfection and the effectiveness of using homemade masks in reducing the transmission of COVID-19. Methods: Search was performed in the MEDLINE, SciELO and Google Scholar databases, in addition to the official recommendations for use. Results: 31 references were included. The filtration capacity of tissues varied between 5 and 98%. 100% cotton fabrics in two or three layers showed filtration efficiency between 70 and 99%, in vitro. Homemade masks, surgical and respirators showed breathability between 2.2 to 3.0 Pascal. The ability to reduce the spread of microorganisms by people wearing home masks was three times less than when using surgical masks, but it was superior to not wearing masks. Conclusion: The breathability of homemade masks may be adequate, while the filtration efficiency seems to be inferior to surgical masks, but superior to no mask use. There is no evidence to support the efficacy and effectiveness of homemade masks.